2017
DOI: 10.1038/s41598-017-11331-9
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of calcifications in breast cancer

Abstract: We investigated the gene expression profiles of calcifications in breast cancer. Gene expression analysis of surgical specimen was performed using Affymetrix GeneChip® Human Gene 2.0 ST arrays in 168 breast cancer patients. The mammographic calcifications were reviewed by three radiologists and classified into three groups according to malignancy probability: breast cancers without suspicious calcifications; breast cancers with low-to-intermediate suspicious calcifications; and breast cancers with highly suspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 61 publications
(52 reference statements)
1
18
0
Order By: Relevance
“…The SKBR3 cell line represents the first identified HER2+ mineralising cell line, an important finding in light of the significant association between HER2 expression and the presence of microcalcifications 15,51 . Interestingly, we did not see positive results in HER2 overexpressing sub-clone of the luminal MCF7 cell line (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The SKBR3 cell line represents the first identified HER2+ mineralising cell line, an important finding in light of the significant association between HER2 expression and the presence of microcalcifications 15,51 . Interestingly, we did not see positive results in HER2 overexpressing sub-clone of the luminal MCF7 cell line (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the particular case of HER2-positive breast tumors, gene profiling studies have shown that highly suspicious calcifications are associated with decreased immune system activity and ERBB2 overexpression [66]. For this reason, breast calcifications would be useful not only in the radiological assessment of breast lesions [67], but also in the management of breast cancer patient candidates for immunotherapy.…”
Section: Breast Tumor Microenvironmentmentioning
confidence: 99%
“…4(b), (c), (d) and Table I Recently, as a classical approach, the crystallization of metal oxide channel layer at a low temperature was developed using a catalytic capping layer such as tantalum (Ta) or titanium (Ti). [12,13] Figure 5 shows the cross-sectional TEM images of the IGZO layer with Ta catalytic layer at different thermal annealing temperatures. The crystallization effect was not seen in the sample at the low temperature of 200 C (Fig.…”
Section: Resultsmentioning
confidence: 99%